The World Bank premises for teacher training: a critical analysis (Research, Society and Development, 2023)
The general objective of this study was to analyze the interventions of the World Bank in teacher training, with the specific objectives: a) to investigate the transformations that occurred in teacher training in developing countries; b) investigate the impacts of changes promoted by the World Bank on teacher training in Brazil; and c) verify the Bank's conditionalities when strengthening capital assumptions. In methodological terms, the research was based on the dialectical historical materialism method, from a qualitative approach and a bibliographic investigation. To this end, the theoretical propositions of the following authors were fundamentally taken as references: Pansardi (2011), Rabelo et al (2015), Corte, Sarturi and Nunes (2018), Freitas (2018), Soares e Silva (2018), Santos and Orso (2020), Zank and Malanchen (2020), among others. The results and discussions pointed out that the educational transformations that occurred in the last decades contribute to the segmentation of teacher training with the pragmatic prototype focused on the experiential knowledge of teachers, depreciating the scientific knowledge that underlies teaching, as well as the indications of international agencies they surround themselves with the limitation of costs and time in education to achieve goals and to proliferate capital gains. In the final considerations, it was emphasized that the changes that took place in Brazilian education have the purpose of carrying out the capital's educational project, with this end in mind, potentiating the opportune transformations for the strengthening of capitalism, thus impacting teacher training in such a way that they directed the training and pedagogical practice, in order to prepare students for the job market.